Gene expression profiling of cytochromes P450, ABC transporters and their principal transcription factors in the amygdala and prefrontal cortex of alcoholics, smokers and drug-free controls by qRT-PCR. (2nd December 2015) - Toselli, Francesca; de Waziers, Isabelle; Dutheil, Mary; Vincent, Marc; Wilce, Peter A.; Dodd, Peter R.; Beaune, Philippe; Loriot, Marie-Anne; Gillam, Elizabeth M. J.
Abstract: 1. Ethanol consumption and smoking alter the expression of certain drug-metabolizing enzymes and transporters, potentially influencing the tissue-specific effects of xenobiotics. 2. Amygdala (AMG) and prefrontal cortex (PFC) are brain regions that modulate the effects of alcohol and smoking, yet little is known about the expression of cytochrome P450 enzymes (P450s) and ATP-binding cassette (ABC) transporters in these tissues. 3. Here, we describe the first study on the expression of 19 P450s, their redox partners, three ABC transporters and four related transcription factors in the AMG and PFC of smokers and alcoholics by quantitative RT-PCR. 4. CYP1A1, CYP1B1, CYP2B6, CYP2C8, CYP2C18, CYP2D6, CYP2E1, CYP2J2, CYP2S1, CYP2U1, CYP4X1, CYP46, adrenodoxin and NADPH-P450 reductase, ABCB1, ABCG2, ABCA1, and transcription factors aryl hydrocarbon receptor AhR and proliferator-activated receptor α were quantified in both areas. CYP2A6, CYP2C9, CYP2C19, CYP3A4, CYP3A5, adrenodoxin reductase and the nuclear receptors pregnane X receptor and constitutive androstane receptor were detected but below the limit of quantification. CYP1A2 and CYP2W1 were not detected. 5. Adrenodoxin expression was elevated in all case groups over controls, and smokers showed a trend toward higher CYP1A1 and CYP1B1 expression. 6. Our study shows that most xenobiotic-metabolizing P450s and associated redox partners, transporters and transcription factors are expressed in human AMG and PFC.